Implementation of Microservices Architecture in Property Rental Marketplace - Brana Pandega; Widyaro, Setyawan (Proceedings of the Informatics Conference, 2026)
Microservices architecture is designed to enhance system flexibility, scalability, and maintainability by breaking down applications into small, independent services. This study analyzes business and technical requirements, designs an appropriate architecture, and tests the performance of each service in a property rental marketplace to ensure the system meets the established criteria. The research findings show that microservices architecture improves development flexibility, allowing updates and fixes to be made without disrupting the entire system. Additionally, this architecture enables each service to be scaled independently, addressing performance issues faced by monolithic systems. However, the implementation of microservices also faces challenges, such as the complexity of inter-service communication and distributed data management. This research concludes that microservices architecture is an effective solution for developing a property rental marketplace, offering advantages in terms of flexibility and scalability. These findings provide practical guidance for developers and project managers and encourage further research to overcome the challenges in implementing microservices.